RANCANG BANGUN SISTEM INFORMASI PENILAIAN KINERJA TENAGA PENDIDIK DI FAKULTAS TEKNIK DAN SAINS UNIVERSITAS IBN KHALDUN - Yuggo Afrianto; Jejen Jaenudin; Novita Br Ginting (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan)
The performance appraisal system is a system to evaluate all resources whether those resources have run following the standards set by management in achieving its objectives. But the need for a mechanism that can facilitate the process of evaluating the performance of educators, and the results of the performance appraisal need to be recorded on an information technology system so that the process of evaluating the performance of educators can be processed quickly and objectively is still an obstacle. The purpose of this study is to obtain an application system design assessment of the performance of educators. The waterfall is a method used in system development. The 360-degree method and k-nearest neighbour are used as models to calculate the performance appraisal of the teaching staff. Sources of data in this study include Questionnaire, DP3 (Daftar penilaian pelaksanaan pekerjaan pegawai). The results of this study are the application of the teacher performance appraisal system has met the feasibility based on black box testing and can assess the performance of educators quickly and objectively.